Preparing Phytosome Curcumin and PEG-CUR Complex - Tung, Bui Thanh; Hai, Nguyen Thanh; Son, Phan Ke (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 34 No 1DO - 10.25073/2588-1132/vnumps.4102, 2018)
Despite curcumin’s numerous pharmacological effects, it has been limitedly used in clinical practice due its low bioavailability. In this study, phytosome curcumin and PEG-CUR complex were prepared to increase their bioavailability. Phytosome curcumin was prepared by reaction between curcumin and phosphatidylcholine; PEG-CUR was prepared by reaction between curcumin and PEG. Phytosome curcumin and PEG-CUR were characterized by 1 H NMR, FTIR and DSC analysis. The physicochemical parameters such as zeta potential, size distribution, solubility and curcumin content were also investigated. The amount of curcumin in phytosome curcumin was 25.71 ± 0.46 % and in PEG-CUR was 13.26 ± 1.25 %. Phytosome curcumin has the size of 131.8 nm and the zeta potential of -48.4 mV, while PEG-CUR has the size of 96.3 nm and the zeta potential of -44.5 mV. The solubility of phytosome curcumin and PEG-CUR in certain media was higher than that of free curcumin. The in vivo assay showed that phytosome curcumin had stronger hepatoprotective effect in comparison with free curcumin. The administration of phytosome curcumin effectively suppressed paracetamol-induced liver injury evidenced by a reduction in lipid peroxidation level, and elevated enzymatic antioxidant activities of superoxide dismutase, catalase, and glutathione peroxidase in mice liver tissues. The study results also show that the cytotoxicity effect of PEG-CUR was much greater than that of free curcumin in HepG2 and HCT116 cancer cell lines. Keywords Curcumin, phytosome, PEGylation, solubility, cytotoxicity, hepatoprotective. References  Chattopadhyay I, Biswas K, Bandyopadhyay U, Banerjee RK. Turmeric and curcumin: Biological actions and medicinal applications. Current science 87(1) (2004) 44. [2] Sasaki J, Kichida M. Curcumin: Biosynthesis, Medicinal Uses and Health Benefits. Nova Science (2012). [3] Dulbecco P, Savarino V. Therapeutic potential of curcumin in digestive diseases. World journal of gastroenterology : WJG 19(48) (2013) 9256. [4] Maheshwari RK, Singh AK, Gaddipati J, Srimal RC. Multiple biological activities of curcumin: A short review. Life Sciences 78(18) (2006) 2081. [5] Çıkrıkçı S, Mozioglu E, Yılmaz H. Biological activity of curcuminoids isolated from Curcuma longa. Rec Nat Prod 2(1) (2008) 19. [6] Weber WM, Hunsaker LA, Abcouwer SF, Deck LM, Vander Jagt DL. Anti-oxidant activities of curcumin and related enones. Bioorganic & Medicinal Chemistry 13(11) (2005) 3811. [7] Han S, Yang Y. Antimicrobial activity of wool fabric treated with curcumin. Dyes and Pigments 64(2) (2005) 157. [8] Anand P, Kunnumakkara AB, Newman RA, Aggarwal BB. Bioavailability of curcumin: problems and promises. Molecular pharmaceutics 4(6) (2007) 807. [9] Kidd PM. Bioavailability and activity of phytosome complexes from botanical polyphenols: the silymarin, curcumin, green tea, and grape seed extracts. Altern Med Rev 14(3) (2009) 226. [10] Jantarat C. Bioavailability enhancement techniques of herbal medicine: A case example of curcumin. International J Pharmacy and Pharmaceutical Sci 5((2013) 493. [11] Choubey A. Phytosome: a novel approach for herbal drug delivery. International Journal of Pharmaceutical Sciences and Research 2(4) (2011) 807. [12] Bhattacharya S. Phytosomes: the new technology for enhancement of bioavailability of botanicals and nutraceuticals. International Journal of Health Research 2(3) (2009) 225. [13] Giori A, Franceschi F. Phospholipid complexes of curcumin having improved bioavailability. Google atents (2007). [14] Pasut G, Sergi M, Veronese FM. Anti-cancer PEG-enzymes: 30 years old, but still a current approach. Advanced drug delivery reviews 60(1) (2008) 69. [15] Pandey MK, Kumar S, Thimmulappa RK, Parmar VS, Biswal S, Watterson AC. Design, synthesis and evaluation of novel PEGylated curcumin analogs as potent Nrf2 activators in human bronchial epithelial cells. European Journal of Pharmaceutical Sciences 43(1–2) (2011) 16. [16] Murphy CJ, Tang H, Van Kirk EA, Shen Y, Murdoch WJ. Reproductive effects of a pegylated curcumin. Reproductive toxicology 34(1) (2012) 120. [17] Phạm Thị Minh Huệ, Bùi Văn Thuấn, Đặng Việt Hùng. Nghiên cứu bào chế phytosome curcumin. Tạp chí dược học467) (2015) 14. [18] Maiti K, Mukherjee K, Gantait A, Saha BP, Mukherjee PK. Curcumin–phospholipid complex: Preparation, therapeutic evaluation and pharmacokinetic study in rats. International Journal of Pharmaceutics 330(1–2) (2007) 155. [19] Murphy CJ, Tang H, Van Kirk EA, Shen Y, Murdoch WJ. Reproductive effects of a pegylated curcumin. Reproductive Toxicology 34(1) (2012) 120. [20] Tang H, Murphy CJ, Zhang B, Shen Y, Sui M, Van Kirk EA, et al. Amphiphilic curcumin conjugate-forming nanoparticles as anticancer prodrug and drug carriers: in vitro and in vivo effects. Nanomedicine 5(6) (2010) 855. [21] Wichitnithad W, Jongaroonngamsang N, Pummangura S, Rojsitthisak P. A simple isocratic HPLC method for the simultaneous determination of curcuminoids in commercial turmeric extracts. Phytochemical Analysis 20(4) (2009) 314. [22] Wichitnithad W, Nimmannit U, Callery PS, Rojsitthisak P. Effects of different carboxylic ester spacers on chemical stability, release characteristics, and anticancer activity of mono‐PEGylated curcumin conjugates. Journal of pharmaceutical sciences 100(12) (2011) 5206. [23] Howell B, Siler S, Shoda L, Yang Y, Woodhead J, Watkins PB. A Mechanistic Model of Drug‐Induced Liver Injury Aids the Interpretation of Elevated Liver Transaminase Levels in a Phase I Clinical Trial. CPT: pharmacometrics & systems pharmacology 3(2) (2014) 1.